Software Applications to Health Sector: A Systematic Review of Literature (2018)
Technology has become a strategic ally for the automation and improvement of processes in the health sector. Many of the current developments have supported the automatic, efficient and efficient detection of different pathologies which results in quality of life and treatment of patients. This study proposes a systematic review of the literature which compiles different developments that have contributed to the solution of different problems in the sector and the advances that have contributed to the processes of continuous improvement of detection and treatment.